العنف الأسري الموجه ضد المرأة وعلاقته بالصلابة النفسية لدى عينة من النساء المعـنفات - بن طاهر, التيجاني; بهياني, مارية يمينة (Sciences de l'Homme et de la Société, 2016)
تتلخص دراستنا الحالية في التطرق إلى متغيرين أساسين وهما العنف الأسري ضد المـرأة والصلابة النفسية، على عينة من النساء المعنفات حيث تم تعريف هذين المتغيرين إجرائيا كالتالي: المتغير الأول هو كل سلوك عـدائي موجه ضد المرأة داخــل الأسرة بقصد إلحــــاق الأذى بهـا أو الضرر سـواء كـان نفسي أو لفظي أو جسـدي أو جنسي أما المتغير الثاني فهو يمثل قدرة المرأة المعنـفة على امتلاك خصائص في شخصيتها تجعلهـا قوية في نفسهـا أمام المشاكل والعقبات، متزنـةـ في الأزمات، حكيمة في المواقف قادرة عـلى تحمل المصائب وكــل الممارسات العدائية الموجهة لها.    Abstract :             Our study aims mainly at treating two essential variables which are domestic violence against women and psychological  hardiness  within a sample of  battered women . The two variables are technical by defined as, for the former,  being any hostile behavior against women in household That aims at harming the her either mentally verbally, corporally ,or sexually .As the for latter, it is  the ability of the battered women to have a strong personality that makes her first tough enough to face whatever an obstacle or a problems she may encounter, then wise and cautions in difficulties and hardship, and finally  able to confront and  resist any aggression or wrongdoing directed against her .